2019
DOI: 10.1186/s12970-019-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported methods of weight cutting in professional mixed-martial artists: how much are they losing and who is advising them?

Abstract: BackgroundSimilar to other combat sports, mixed martial arts (MMA) includes divisional weight classes. The purpose of our research was to further investigate the amount of weight professional MMA fighters lost prior to weighing in for competition, their methods used to cut weight, and their sources of advice on how to cut weight.MethodsThis survey was administered to 92 male professional MMA athletes. The survey questions included duration of overall weight loss prior to competition, methods of weight-cutting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…The most common weight loss strategy was maintaining a negative energy balance (through limiting food intake and/or increasing physical activity). Similar conclusions were drawn from studies involving athletes from other combat sports: box, Brazilian jiu-jitsu, wrestling, judo, Muay Thai/kickboxing and mixed martial arts [2,[34][35][36][37][38].…”
Section: Weight Loss Methodssupporting
confidence: 72%
“…The most common weight loss strategy was maintaining a negative energy balance (through limiting food intake and/or increasing physical activity). Similar conclusions were drawn from studies involving athletes from other combat sports: box, Brazilian jiu-jitsu, wrestling, judo, Muay Thai/kickboxing and mixed martial arts [2,[34][35][36][37][38].…”
Section: Weight Loss Methodssupporting
confidence: 72%
“…It is essential that registered dietitians are involved in this process as they are qualified to advise proper fuelling and weight loss. Similar to previous studies [1,7,9,13,19,24], registered dietitians were found to be an underutilised resource in this group of Silat athletes. Access to registered dietitians for sport-specific weight loss advice is limited as many countries lack sport dietitians.…”
Section: Discussionsupporting
confidence: 87%
“…Cut off scores to indicate the It is notable that in the entire sample of 102 Silat athletes, only 24.5% engaged in pre-competition weight loss compared to the > 90% prevalence reported in other combat sports [9,13,19,28]. Remarkably, only 4% of the current sample engaged in acute weight loss compared to 30% reported by Park et al [19]. Furthermore, the use of risky weight management practices such as laxatives, diet pills and vomiting were uncommon.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…These practices differ across each sport, depending on the distance between the weighting procedure and the match, so the RWL could start 2–3 days before the competition and the RWG could last from 1 to 18 h [ 8 ]. It has been reported that combat sports athletes have performed this practice at least once in life [ 9 , 10 ], but this methodology is also known among amateur fighters and it is applied from two to eight times per year (personal communication and experience within the Italian Muay Thai and Italian Boxing federations). The goal of cutting weight is to be able to compete in a lower-weight category than one of the regular season, which would translate into a physical advantage; notwithstanding, scientific literature has demonstrated a reduction in sports and psychological performance after drastic RWL and RWG [ 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%